MARKETING STRATEGY TRAINING FOR MSMES IN LHOKSEUMAWE CITY - Safwan; Yusnidar; Azhari; Almunadiya; Rahmiatul Aula; Noratul (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2025)
Many MSMEs in Lhokseumawe City still lack effective marketing management, and many women in the Family Welfare Movement (PKK) are unemployed. This demonstrates the potential for entrepreneurship development in Lhokseumawe City. The purpose of Community Service is to motivate the community to become interested in entrepreneurship by utilizing existing potential. The targets are MSMEs, unemployed housewives, and PKK women. The benefits of Community Service are expected to encourage MSMEs and housewives to become entrepreneurial, to be able to start and run businesses, and to assist the government in reducing unemployment. The methods used for implementing community service activities include training, lectures, and discussions. Community service activities will be implemented in the even semester of 2024-2025.